PENYEBAB DAN DAMPAK PENURUNAN KOGNITIF PADA KUALITAS HIDUP LANSIA - Panggayuh, Ganesha Lintang; Putri Junio, Zakia; Aqila Naila Ismail, Sachiko; Suparmi, Suparmi (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2025)
The decline in cognitive function in the elderly is known by the appearance of signs and symptoms in the form of memory impairment, changes in perception, problems in communicating, and decreased focus and attention. This study aims to identify causal factors and analyze the impact of cognitive decline on the quality of life of the elderly. With a better understanding of the relationship between cognitive function and quality of life. This research was conducted by conducting a literature review by searching for articles relevant to the research topic and sourcing from various sources of articles published in the last ten years obtained in the publish or perish application. Data was obtained from Google Scholar by getting 7 articles that match the research theme. This study identified elderly aged ≥60 years who experienced cognitive decline, except those with severe communication impairment who were unable to provide the required information. Data analysis was then combined with narrative to create a report that answered the research objectives. That cognitive decline in the elderly affects the quality of life of the elderly which causes dependence on others. Decreased cognitive function is usually caused by several factors, namely age, education factors, and health factors.